Postdischarge symptoms and rehabilitation needs in survivors of COVID‐19 infection: A cross‐sectional evaluation. Issue 2 (17th August 2020) - Halpin, Stephen J.; McIvor, Claire; Whyatt, Gemma; Adams, Anastasia; Harvey, Olivia; McLean, Lyndsay; Walshaw, Christopher; Kemp, Steven; Corrado, Joanna; Singh, Rajinder; Collins, Tamsin; O'Connor, Rory J.; et al.
Abstract: Background: There is currently very limited information on the nature and prevalence of post‐COVID‐19 symptoms after hospital discharge. Methods: A purposive sample of 100 survivors discharged from a large University hospital were assessed 4 to 8 weeks after discharge by a multidisciplinary team of rehabilitation professionals using a specialist telephone screening tool designed to capture symptoms and impact on daily life. EQ‐5D‐5L telephone version was also completed. Results: Participants were between 29 and 71 days (mean 48 days) postdischarge from hospital. Thirty‐two participants required treatment in intensive care unit (ICU group) and 68 were managed in hospital wards without needing ICU care (ward group). New illness‐related fatigue was the most common reported symptom by 72% participants in ICU group and 60.3% in ward group. The next most common symptoms were breathlessness (65.6% in ICU group and 42.6% in ward group) and psychological distress (46.9% in ICU group and 23.5% in ward group). There was a clinically significant drop in EQ5D in 68.8% in ICU group and in 45.6% in ward group. Conclusions: This is the first study from the United Kingdom reporting on postdischarge symptoms. We recommend planning rehabilitation services to manage these symptoms appropriately and maximize the functional return of COVID‐19 survivors. Highlights: This is the first UK study reporting on longer term symptoms in individuals recovering from COVID‐19. New illness‐related fatigue, breathlessness and psychological distress were commonly reported at 7 weeks after discharge from hospital with a clinically significant drop in the quality of life of many individuals. Symptoms were present in both ward and ICU managed individuals, the prevalence being higher in those who required ICU care. Rehabilitation care for COVID‐19 survivors must therefore be need‐focused, delivered by specialist multidisciplinary team and planned for the longer term to meet the needs of these individuals.